Russia's government budget swings around elections and recessions - Vesa Korhonen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
This policy brief examines the shifts in Russia's government budget flows around election times and economic recessions. The issue is intriguing as Russia has basically pursued a policy of maintaining budget surpluses. Indeed, the government budget sector has shown a positive net financial stock for many years – a rare achievement for almost any country. Large downward and upward shifts in revenue and expenditure have induced sizeable changes in the balance, although in recent years swings in budget revenues have decreased as non-oil revenue streams gained importance.The real volume of government budget expenditure increased strongly around election time a decade ago. Such spending accelerations faded by the election cycle of autumn 2016 to early 2018 and remained subdued around the Duma elections in autumn 2021. Counter-cyclical budget spending policies were implemented around the 2009 and 2020 recessions to contain economic harms. The stimulus focus was on social benefits and corporate subsidies. Russia's spending increases in real terms around the 2009 recession reached the mid-range of increases when compared to twelve European economies and the US. During the 2020 recession, Russia's increases were short-lived and fell short of the hikes in almost all 13 comparison countries relative to size of GDP, but not drops in GDP.
urn:nbn:fi:bof-202202141060
Keywords: 330; Russia; government budget; recession; election